The Concept of Dilthey’s Hermeneutics as Reflected in Juliasih’s Potensi Perempuan Amerika (Tinjauan Feminisme) - M Afifulloh (Faculty of Social and Political Sciences University of Bangka Belitung, 2019)
This paper aims at the description of Dilthey’s hermeneutics concept in the book entitled “Potensi Perempuan Amerika (tinjauan feminisme)”. This research is qualitative descriptive research. The data were analyzed by Dilthey’s hermeneutic approach. The result showed that in understanding and interpreting meaning, there are 3 formulas that can be used as interpretive methods according to Dilthey, namely Erlebnis (living experience), Ausdruck (expression), and Verstehen (understanding). The experience referred to here is the life history of the author, everything that was experienced by the director during his lifetime. The expressions are works written by the author through the language used to voice their desires, opinions, and actions. Understanding is the process of bringing together all the data generated from the process of experience and expression so that it can draw conclusions. In the book of Juliasih Kusharyanto, the three main aspects of the hermeneutics have been carried out well so that at the end of the research, Juliasih was able to provide a complete meaning from the historical side as well as language expressions that exist in the storyline of each novel studied.